2007
DOI: 10.1017/s0016774600021326
|View full text |Cite
|
Sign up to set email alerts
|

The influence of floodplain morphology and river works on spatial patterns of overbank deposition

Abstract: Floodplain topography and related hydraulic patterns of overbank flow constitute a major control on the amounts and patterns of sediment deposition on floodplains. We studied the differences in sediment deposition at two scales along two river branches of the lower River Rhine in the Netherlands: the Waal and IJssel River. Human alterations like levelling and embankment construction have severely impacted the floodplains along the Waal River branch (average discharge: 1500 m 3 ·s -1 ), whereas the relatively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
7
13
0
2
Order By: Relevance
“…Furthermore, a significant negative trend between sedimentation and the height of the location was found, which has also been reported by French and Spencer (1993), Middelkoop and van der Perk (1998), Reed et al (1999), Temmerman et al (2003), and Thonon et al (2007). Although the height and distance from the channel do control sedimentation, their influence is not as strong as observed in most marshes or river floodplains.…”
Section: Patterns In Sedimentationsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, a significant negative trend between sedimentation and the height of the location was found, which has also been reported by French and Spencer (1993), Middelkoop and van der Perk (1998), Reed et al (1999), Temmerman et al (2003), and Thonon et al (2007). Although the height and distance from the channel do control sedimentation, their influence is not as strong as observed in most marshes or river floodplains.…”
Section: Patterns In Sedimentationsupporting
confidence: 71%
“…This table suggests that sedimentation is positively related to the suspended sediment concentration. Furthermore, it is widely known from the literature that sedimentation is controlled by the frequency and duration of inundation (French and Spencer, 1993;Middelkoop and van der Perk, 1998;Reed et al, 1999;Temmerman et al, 2003;Thonon et al, 2007), the suspended sediment concentration in the feeding channel French and Spencer, 1993), and the ability of sediment to settle, which is in turn controlled by vegetation (Darke and Megonigal, 2003;Temmerman et al, 2005b;Schile et al, 2014;Mitsch et al, 2014), the flow paths to or within the wetland/compartment (French and Spencer, 1993;Siobhan Fennessy et al, 1994;Reed et al, 1999;Davidson-Arnott et al,2002;Temmerman et al, 2003;Anderson and Mitsch, 2007;Mitsch et al, 2014), and the residence time within the compartment (Asselman and Van Wijngaarden, 2002). Although considerable research has been devoted to sedimentation in wetlands in coastal deltas and river floodplains, remarkably few empirical field studies have been reported on the initial formation and evolution of newly created wetlands.…”
mentioning
confidence: 99%
“…The inverse relationship between elevation and sedimentation rate (Walling et al, 1996;Walling and He, 1998) could not be confirmed by this study. As Middelkoop and Asselman (1998) and Thonon et al (2007b) found, this might be attributed to levees and other topographic features. Moreover, high flow velocities at low-lying areas can even reverse this trend at certain flood magnitudes (Asselman and Middlekoop, 1998).…”
Section: Linear Mixed-effect Modelsmentioning
confidence: 82%
“…Previous studies have indicated that sediment deposition in wetlands is controlled by various factors including the flooding frequency, depth, and duration (French and Spencer 1993;Middelkoop and van der Perk 1998;Reed et al 1999;Temmerman et al 2003;Thonon et al 2007;Schuerch et al 2013), the surface area of the wetland, the suspended sediment load (French and Spencer 1993;Asselman and Middelkoop 1998;Morse et al 2004;Noe et al 2016), and the ability of sediment to settle, which in turn, depends on sediment flow paths (French and Spencer 1993;Siobhan Fennessy et al 1994;Reed et al 1999;Davidson-Arnott et al 2002;Temmerman et al 2003;Anderson and Mitsch 2007;Mitsch et al 2014), wind (Orson et al 1990;Delgado et al 2013), and vegetation (Darke and Megonigal 2003;Temmerman et al 2005;Schile et al 2014;Mitsch et al 2014). These studies were mainly conducted in salt marshes or river flood plains; only few field-based studies were undertaken in freshwater tidal wetlands that represent the transition between these environments.…”
Section: Introductionmentioning
confidence: 99%